Identification, Impacts, and Control of Ragweed Parthenium (Parthenium hysterophorus L.) - Robert H. Stamps (EDIS)
One of the world’s most invasive weeds, this member of the Asteraceae family is a problem in Africa, Australia, India, and is increasingly a problem in Florida. Learn more in this 10-page fact sheet written by Robert H. Stamps, and published by the UF Department of Environmental Horticulture, December 2011.